(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Cellulose and its derivatives have gained prominence in the oil and gas industry due to their versatility and effectiveness in various applications. This article explores the synthesis, properties, and applications of cellulose-based reagents, focusing on their roles in drilling, cementing, fracturing, and wastewater treatment processes. The review highlights recent advancements and the potential of these biopolymers in enhancing operational efficiency and environmental sustainability within the sector.